The Effect of Employing the Ishikawa’s Diagram in Teaching History to Develop Productive Thinking and Engagement in Learning Among Students - Alshamasneh, Wesam Mosleh Faleh; Obeidat, Hani Hatmel (Journal of Ecohumanism, 2025)
The study aimed to identify the use of Ishikawa’s diagram while teaching history to develop productive thinking and engagement in learning among students. The quasi-experimental approach was followed to achieve this goal, where study tools were built, represented by the productive thinking test, which consisted of (22) questions, and the engagement in learning scale, which consisted of (44) items, and were both verified for their validity and reliability. These tools were applied to a group of the study population consisted of (54) female students from the tenth grade at Umm Kulthum Mixed School in the First Zarqa District, where they were divided into two groups: the experimental group studied using Ishikawa’s diagram and consisted of (27) female students, and the control group studied using the traditional method and consisted of (27) female student. The results of the study showed that there were statistically significant differences between the mean grades of the first experimental group, the control group in the productive thinking test, and the engagement in learning scale in favor of the experimental group that was taught using Ishikawa’s diagram. The study recommended the need to encourage history teachers to employ Ishikawa’s diagram strategy while teaching history because of its positive impact on developing productive thinking and raising the level of engagement in learning.